The Effectiveness of Meniran (Phyllanthus niruri) and Gotu Kola (Centella asiatica) Herbs on Broiler Chicken Performance - Puji Astuti; Diwi Acita Irawati (BANTARA JOURNAL OF ANIMAL SCIENCE, 2022)
This study aims to determine the performance of broiler chickens given Phyllanthus niruri and Centella asiatica extracts. The research was conducted for 32 days at the Animal Husbandry Practice Unit (UPT) of the Karanganyar Animal Husbandry Academy. The material used was 100 broiler Cobb strains aged 4 days, kept in 20 experimental units, each unit consisting of 5 chickens with an average initial weight of 111,08 ± 4.74 g. The first treatment (T0) control, chicken without giving P. niruri and C. asiatica extracts, the second treatment (T1) the chicken was given 10 ml P. niruri extract per liter of drinking water, the third treatment (T2) the chickens were given 5 ml P. niruri extract and 5 ml C. asiatica  extract, per liter of drinking water, the fourth treatment (T3) of chickens was given C asiatica extract 10 ml per liter of drinking water. The variables observed included drinking water consumption, feed consumption, average daily gain, and feed convertion ratio (FCR). The design used was a completely randomized design (CRD). The data were analyzed for variety and if there was a significant effect of the treatment, it was continued with the Duncan Multiple Distance Test to determine differences in treatment. The results showed that drinking water consumption, and average daily gain were not significantly different between treatments, feed consumption (g/head/day) and feed convertion ratio was significantly different between treatments. The conclusion of this research is that giving P. niruri and C. asiatica extracts in drinking water   affect the performance of broiler chicken.